(untitled) (Journal of Medical & Health Sciences Review, 2025)
Dyspepsia, commonly known as indigestion, is a prevalent gastrointestinal disorder that significantly affects quality of life. This study assessed the contributing factors and clinical manifestations of dyspepsia in Shangla District, Pakistan, and evaluated the effectiveness of health education in improving outcomes. A descriptive study was conducted on 50 patients (30 female, 20 male) attending the District Headquarter Hospital Alpuri. Data were collected through questionnaires, clinical examinations, and follow-ups after health education interventions. Findings revealed higher prevalence of dyspepsia among women, especially in childbearing age, and among illiterate individuals. Major risk factors included NSAID use (74%), smoking (42%), poor dietary habits, and pregnancy (37%). Clinical symptoms included nausea, heartburn, reflux oesophagitis, belching, and pain after meals. Health education significantly improved patient outcomes, reducing symptom prevalence by 76% overall. The study concludes that health education is a cost-effective strategy to prevent and manage dyspepsia in resource-limited settings.